Vitamin D - knowledge among people about its properties and effects based on anonymous surveys - Agnieszka Grużewska; Kinga Grużewska-Piotrowska (Nicolaus Copernicus University in Toruń, 2023)
Introduction: Vitamin D is produced under the influence of solar radiation. It can also be supplied in food or dietary supplements. The assessment of total serum 25(OH)D is widely accepted as an indicator of vitamin D concentration and observation of the population regarding hypovitaminosis or recommendations regarding supplementation. In fact, the definition of vitamin D deficiency is still a contentious issue, however, epidemiological data indicate that vitamin D deficiency is widespread worldwide, including Poland. The aim of the study: The aim of the study was to assess the knowledge of people about supplementation and the effects of vitamin D, its deficiency and consumed nutrients, in which it is found, based on anonymous surveys. Materials and methods: The research material was collected using an anonymous online survey in April and May 2023. The obtained results were analyzed and verified on the basis of scientific literature and statistically processed using Microsoft Office Excel. Results: 47.3% of the respondents take dietary supplements with vitamin D, but 76% of these people do not know the dose they are taking. More than half of them declare knowledge of the function of vitamin D3, of which 70.3% of respondents correlate the effect of cholecalciferol with the skeletal system. 50.2% of people eat fish rarely or not at all. 68.5% of respondents claim that vitamin D should be supplemented with vitamin K to be effective. Discussion and conclusions: Less than half of the respondents take preparations containing vitamin D. Few people know the full use of vitamin D in the body and its multidirectionality. More than half of the respondents do not know the effects of hypovitaminosis D. Prevention of vitamin D deficiency should be reintroduced due to lifestyle changes, e.g. after the COVID-19 pandemy. Keywords: vitamin D, hypovitaminosis, cholecalciferol, calcium